O grupo araxá na região sul-sudoeste do estado de goiás - Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; Da Conceição, Fabiano Tomazini [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
In the S - SW region of Goiás State, Brazil, the Araxá Group is constituted of a metasedimentary sequence containing schistose and gneissic (garnet-biotite-quartz schists, feldspatic garnet-biotite-quartz schists, garnet-biotite-quartz paragneisses, with muscovite and locally amphibole, epidote, kyanite and staurolite. This sequence presents intercalations of metaul-tramafc rocks (serpentinite, actinolite schist, talc schist, chlorite schist), metamafc ones (amphibolite, amphibole schist containing or not garnet, garnet amphibolite) and associated granitic bodies. Chemically, the Araxá Group metasediments present peraluminous composition, showing enrichment in LILE, when compared with HFSE and REE, and displaying negative anomalies of Nb, Ta, Sr, P and Ti. Their chemical composition is that of greywake and the chemical characteristics of the sediments are generated in magmatic arcs. Isotopic data for Sm/Nd - model ages (TDM) between 1,04 - 1,51 and 1,76 - 2,26 Ga - and U/Pb (predominance of zircon with ages < 900 Ma) suggest that these metasediments have Neoproterozoic rocks as the source rocks. Chemical and isotopic characteristics of the studied metasediments suggest that their source are rocks originated in magmatic arcs and that they were deposited in a fore arc basin developed in the margins of Neoproterozoic island arcs.
The araxá group in the south-southwest region of the goiás state
Keywords: Araxágroup; Brasília Belt; Geochemistry; Geochronology Sm/Nd and U/Pb